MICROWAVE-ASSISTED SYNTHESIS AND BIOLOGICAL EVALUATION OF NOVEL PYRAZOLE–THIOSEMICARBAZONE SCHIFF BASES AS POTENTIAL ANTICANCER AGENTS - Hanoon, Aseel G.; Abid, Dawood S. (Antis-Publisher, 2026)
Objective: Primary processes were involved in the synthesis and identification of Schiff bases derivatives obtained from thiosemicarbazide. Method: Three compounds were synthesized using a microwave assisted method, ((E)-2-((3-(4-bromophenyl)-1-phenyl-1H-pyrazol-4-yl)methylene)hydrazine-1 carbothioamide (BT); (E)-2-((1-(4-chlorophenyl)-3-(m-tolyl)-1H-pyrazol-4-yl)methylene)hydrazine-1-carbothioamide (CMT); and (E)-2-((1-(4-chlorophenyl)-3-(4-nitrophenyl)-1H-pyrazol-4-yl)methylene)hydrazine-1-carbothioamide (CNT). FT-IR, ¹H-NMR, ¹³C-NMR, mass spectrometry, recrystallization of the generated compounds, and TLC monitoring of the chemical process were used to identify the chemical structure of the compounds. Anticancer activity using human lung cancer cells A549 through MTT assay to estimate IC50 value for each compound. Results: The results showed that compound BT (1) had a lower IC50 value 53.03 µM. Novelty: Perspective research required to develop compound BT with a mechanistic investigation.